The Influence of Institutional Constraints on Outsourcing - BALAKRISHNAN, RAMJI; ELDENBURG, LESLIE; KRISHNAN, RANJANI; SODERSTROM, NAOMI (Journal of Accounting Research, 2010)
ABSTRACT Drawing on transaction cost economics and institutional theory we argue that the effects of institutional constraints on the transaction costs of outsourcing vary systematically with the type of service outsourced and the ownership structure of the outsourcing firm. Using data from hospitals, we demonstrate that these effects lead to a higher extent of outsourcing of nonclinical compared to clinical services, and larger outsourcing response of nonclinical services to cost pressures from managed care. Further, the effects of ownership structure and associated governance mechanisms on institutional constraints are reflected in the empirical results as cross‐sectional variations in the extent to which outsourcing is invoked as a response to cost pressures by hospitals of different ownership.